Molecular Docking, Drug-Likeness Analysis, In Silico Pharmacokinetics, and Toxicity Studies of p-Nitrophenyl Hydrazones as Anti-inflammatory Compounds against COX-2, 5-LOX, and H+/K+ ATPase - Sodeeq Babalola; Nosakhare Igie; Isaiah Odeyemi (Georg Thieme Verlag KG, 2022)
Nonsteroidal anti-inflammatory drugs (NSAIDs) and coxibs are traditional medicines for the treatment of inflammation, yet associated with serious side effects. Hence, the need for discovering novel compounds with valuable clinical benefits is of great importance. In this study, 18 derivatives of p-nitrophenyl hydrazones were docked against COX-2, 5-LOX, and H+/K+ ATPase, followed by predicting their drug-likeness and absorption, distribution, metabolism, and excretion (ADME) properties. From the docking analysis, 1-(4-nitrophenyl)-2-[(3,4,5-trimethoxyphenyl)methylidene]hydrazine (3), 4-hydroxy-2-methyl-6-[(2-(4-nitrophenyl)hydraz-1-ylidene)methyl]thiochroman-1,1-dioxide (6), 4-methoxy-2-methyl-6-[(2-(4-nitrophenyl)hydraz-1-ylidene)methyl]thiochroman-1,1-dioxide (8), 2-methyl-6-[(2-(4-nitrophenyl)hydraz-1-ylidene)methyl]-4-(trifluoromethyl)thiochroman-1,1-dioxide (11), 4-[(2-(4-nitrophenyl)hydraz-1-ylidene)methyl]benzenesulfonamide (13), 4-[(2-(4-nitrophenyl)hydraz-1-ylidene)methyl]-3-(trifluoromethyl)benzenesulfonamide (14), 5-methyl-6-{4-[(2-(4-nitrophenyl)hydraz-1-ylidene)methyl]phenyl}-2,3,4,5-tetrahydropyridazin-3-ol (16), and 5-methyl-6-{4-[(2-(4-nitrophenyl)hydraz-1-ylidene)methyl]phenyl}-4,5-dihydropyridazin-3(2H)-one (17) showed promise as potent multi-target inhibitors of COX-2, 5-LOX, and H+/K+ ATPase. These compounds are less COX-2 selective than the control (celecoxib). "Drug-likeness" analysis passed Lipinski's, Egan's, Veber's, Muegge's, and Ghose's rules. The compounds also passed Pfizer and GSK rules, as well as golden triangle's rule for identification of potent and metabolically stable drugs. The pharmacokinetic profiles of the compounds were excellent, safe, and compliant with their potential anti-inflammatory activity. The results of the study can be used for future optimization of those derivatives for better molecular interactions against COX-2, 5-LOX, and H+/K+ ATPase, and inflammation-effective inhibition.